2016
DOI: 10.1177/1087054716653214
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socioeconomic Status on Psychological Distress in Canadian Adults With ADD/ADHD

Abstract: The findings suggest that negative outcomes associated with ADD/ADHD are not necessarily pervasive. High income may serve as a protective factor for psychological distress among adults with ADD/ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
9
0
3
Order By: Relevance
“…The fact that only one person in this study worked full time (being selfemployed) and the others worked part time or not at all, is similar to findings by Halmøy, Fasmer, Gillberg, and Haavik (2009). Results from a Canadian study suggest that if conditions are put in place-helping people with ADHD succeed and earn higher incomes-they may not experience aboveaverage levels of psychological distress, meaning that high income may serve as a protective factor for psychological distress (Pond, Fowler, & Hesson, 2019).…”
Section: According Tosupporting
confidence: 73%
“…The fact that only one person in this study worked full time (being selfemployed) and the others worked part time or not at all, is similar to findings by Halmøy, Fasmer, Gillberg, and Haavik (2009). Results from a Canadian study suggest that if conditions are put in place-helping people with ADHD succeed and earn higher incomes-they may not experience aboveaverage levels of psychological distress, meaning that high income may serve as a protective factor for psychological distress (Pond, Fowler, & Hesson, 2019).…”
Section: According Tosupporting
confidence: 73%
“…Another study also found that those socio-economically disadvantaged were most likely to report disability in relation to their intellect and emotions [5]. Concerning psychological distress, other studies also have found a lower prevalence among individuals with high incomes groups compared to those who belong to low income groups [47][48][49].…”
Section: Discussionmentioning
confidence: 89%
“…Como se evidencia en la Tabla, 10 estudios indagaron los factores protectores y de riesgo del TDAH y los síntomas asociados y 1 estudio los examinó en conjunto con una muestra de individuos con TC. 7 estudios identificaron factores protectores (Carballo et al, 2013;Golmirzaei et al, 2013;Mitchell, Cooley, Evans, y Fite, 2016; Muñoz-Pérez, Pérez-García, Arroyo, Vichido-Luna, y Soto-Vega, 2014; Schei, Novik, Thomsen, Indredavik, y Jozefiak, 2015; Zendarski, Sciberras, Mensah, y Hiscock, 2017b) y 6 estudios identificaron factores de riesgo (Carballo et al, 2013;Golmirzaei et al, 2013;Mulraney, Zendarski, Mensah, Hiscock, y Sciberras, 2017;Muñoz-Pérez et al, 2014;Pond, Fowler, y Hesson, 2016;Zendarski, Sciberras, Mensah, y Hiscock, 2017a).…”
Section: Trastorno De Déficit De Atención E Hiperactividad (Tdah)unclassified
“…El estudio fue de carácter transversal y participaron 140 niños entre los 5 y 13 años, quienes fueron evaluados con un cuestionario de dificultades y fortalezas. Por su parte, Pond et al (2016) en un estudio correlacional con una muestra de 488 adultos entre los 20 y 64 años con diagnóstico de TDAH, identificaron que la angustia psicológica asociada a los bajos ingresos económicos incrementan el riesgo de presentar otros trastornos psiquiátricos. De igual forma, otros factores como el nacimiento antes de la semana 37 de gestación (Muñoz-Pérez et al, 2014), ser el primogénito (Carballo et al, 2013), antecedentes parentales de trastornos psiquiátricos, abortos previos, exposición a alcohol y tabaco durante el embarazo, epilepsia y traumas craneales (Golmirzaei et al, 2013) también se relacionan como probables factores de riesgo.…”
Section: Carballo Et Al (2013)unclassified
See 1 more Smart Citation